Theoretical and methodological approaches to the study of personal and professional development of a teacher - Dusmamatov, Bekzod (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In the conditions of modern reality, when the problem of improving personal and professional development becomes extremelyimportant in pedagogical psychology, as in other Sciences, its further development is important for solving the tasks that are set by theprofessional activity of a teacher